The advanced mobile application testing environment. - Binder, Robert V. (Software engineering notes.)
The Advanced Mobile Application Testing Environment (AMATE) combines model-based test generation and evaluation, controllable RF airlink variation, and a robust standards-based distributed test harness for end-to-end testing of distributed mobile applications. This report summarizes AMATE capabilities.